The Blizzard of the World: COVID-19 and the Last Say of the State of Exception - Tacik, Przemysław (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The paper aims to grasp the COVID-19 pandemic as a socio-political catastrophe in the Benjaminian sense. As argued in the article, the scope and nature of the COVID-19 crisis eludes us due to our closeness to its inner core. What is obfuscated in this moment is the politico-legal framework on which the international community is based, where sovereignty and turbocapitalism join their forces to produce biopolitical devices. The paper looks into uses of the state of exception in particular countries, concluding that the rule of law in the pandemic was generally put on the back burner even by the countries that officially praise it. Sovereignty clearly returned to the stage, undermining parliamentarism and civil liberties in the sake of necessity. International law remained incapable of addressing this return, let alone of enforcing responsibility of China for infringing WHO rules. As a conclusion the paper argues that COVID-19 opened new-old paths of governing the living that will play a planetary role in the future fights for dominance and imposing a new face of capitalism.